ANALISIS HUBUNGAN ANTARA EKSTENSIFIKASI WAJIB PAJAK DAN SURAT SETORAN PAJAKDENGAN PENERIMAAN PAJAK(STUDI KASUS PADA KANTOR PELAYANAN PAJAK JAKARTA PALMERAH) - Deddy Arief Setiawan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2007)
Taxes revenue is the main source domestic revenue because stale revenue from taxation sector is a great deal from side state budget as a whole which decanted in State Revenue and Expenditure Budget (APBN). The tax reform with the strategy in internal consolidation and canvassing was used by The Directorate General of Taxes (Direktorat Jenderal Pajak) to obtain faxes revenue. The goal of this research is to observe the number oftaxpayers and the number of tax payment slip that can influence the tax revenue. The basis of the theory is literature, tax regulation, opinion from researcher or who was expert in the field of taxation. Hypothesis test used The Correlation of Pearson Product Moment Analysis.. Recording to the research there is the relationship ffnearly between the number of taxpayer and the number of tax payment slip with the tax revenue.Keywords: Taxpayer, Tax Papent Slip, Tax Revenue